2010
DOI: 10.1088/0031-9155/55/16/s02
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric verification and clinical evaluation of a new commercially available Monte Carlo-based dose algorithm for application in stereotactic body radiation therapy (SBRT) treatment planning

Abstract: Modern cancer treatment techniques, such as intensity-modulated radiation therapy (IMRT) and stereotactic body radiation therapy (SBRT), have greatly increased the demand for more accurate treatment planning (structure definition, dose calculation, etc) and dose delivery. The ability to use fast and accurate Monte Carlo (MC)-based dose calculations within a commercial treatment planning system (TPS) in the clinical setting is now becoming more of a reality. This study describes the dosimetric verification and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 46 publications
3
56
0
Order By: Relevance
“…The method of tissue heterogeneity correction and the dose calculation algorithm are two important factors that affect the dose accuracy in lung SBRT. Several investigators have reported that the MC algorithm in the iPlan improved the dose calculation accuracy when compared to the PB algorithm 13 , 14 , 15 . In both homogeneous and heterogeneous phantoms, excellent agreements between the MC calculations and experimental measurements were reported in both high‐dose and high‐dose‐gradient regions.…”
Section: Discussionmentioning
confidence: 99%
“…The method of tissue heterogeneity correction and the dose calculation algorithm are two important factors that affect the dose accuracy in lung SBRT. Several investigators have reported that the MC algorithm in the iPlan improved the dose calculation accuracy when compared to the PB algorithm 13 , 14 , 15 . In both homogeneous and heterogeneous phantoms, excellent agreements between the MC calculations and experimental measurements were reported in both high‐dose and high‐dose‐gradient regions.…”
Section: Discussionmentioning
confidence: 99%
“…For each plan, the chosen isodose line conformally covered the PTV. Therefore, after a total of 48 plans were created for the 12 patients using the iPlan PB algorithm, all plans were also recalculated using the iPlan MC algorithm (28) with the original MLC apertures and monitor units. The calculated dose differences between the PB and MC dose algorithms were then compared among the four plans prescribed to the varying isodose lines (60%–90%) for each patient.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we sought not to compare RTOG dosimetric compliance criteria on PTV coverage, understanding the fact that PB‐hete overpredicted the PTV coverage, underdosing the target volume that was consistent with aforementioned referenced literature 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 comparing the two algorithms.…”
Section: Methodsmentioning
confidence: 99%
“…There have been several studies reported in the literature on clinical validation of XVMC dose calculations in both homogenous and heterogeneous media utilizing the iPlan RT dose planning system 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 . In recent studies by Sethi and colleagues, (9) XVMC algorithm‐based calculation was scaled using ion chamber and EDR films in various depths in five different phantoms with four different density materials irradiated with 6 MV photons.…”
Section: Introductionmentioning
confidence: 99%